Effects of Meal Fructose/Glucose Composition on Postprandial Glucose Appearance and Hepatic Glycogen Synthesis in Healthy Subjects - Barosa, Cristina; Ribeiro, Rogério T.; Andrade, Rita; Raposo, João F.; Jones, John G. (Journal of clinical medicine, 2021)
Dietary fructose overshadows glucose in promoting metabolic complications. Intestinal fructose metabolism (IFM) protects against these effects in rodents, by favoring gluconeogenesis, but the extent of IFM in humans is not known. We therefore aimed to infer the extent of IFM by comparing the contribution of dietary fructose to systemic glucose and hepatic glycogen appearance postprandially. Twelve fasting healthy subjects ingested two protein meals in random order, one supplemented with 50 g 5/95 fructose/glucose (LF) and the other with 50 g 55/45 fructose/glucose (HF). Sources of postprandial plasma glucose appearance and hepatic glycogen synthesis were determined with deuterated water. Plasma glucose excursions, as well as pre- and post-meal insulin, c-peptide, and triglyceride levels were nearly identical for both meals. The total gluconeogenic contribution to plasma glucose appearance was significantly higher for HF versus LF (65 ± 2% vs. 34 ± 3%, p < 0.001). For HF, Krebs cycle anaplerosis accounted for two-thirds of total gluconeogenesis (43 ± 2%) with one-third from Triose-P sources (22 ± 1%). With LF, three-quarters of the total gluconeogenic contribution originated via Krebs cycle anaplerosis (26 ± 2%) with one-quarter from Triose-P sources (9 ± 2%). HF and LF gave similar direct and indirect pathway contributions to hepatic glycogen synthesis. Increasing the fructose/glucose ratio had significant effects on glucose appearance sources but no effects on hepatic glycogen synthesis sources, consistent with extensive IFM. The majority of fructose carbons were converted to glucose via the Krebs cycle.